Analysis of Examples Used in Textbooks: The Case of Limit - Sevilay Alkan, Bülent Güven, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
In this study, it has been aimed to determine the example types on the subject of limits that are used by mathematics textbooks that based on different mathematics curriculum. In this way, the reflection of the change emerged in the curriculums on textbooks and also on in-class implementations in an indirect way are tried to be rendered through the examples. Within this framework, the examples on the subject of limits given in the 11th grade mathematics textbook (high school 3rd grade) of the academic year 2000-2001 and 12th grade mathematics textbook taught in the academic years of 2009-2010 and 2015-2016 have been examined. In order to determine the example types on the subject of limits that are used in the textbooks, classification on example types developed by Alkan (2016) has been used. In the direction of the research findings, it has been determined that standard and improving examples are frequently used in the textbooks despite the fact that start up examples and non-examples are rarely used. In addition to this, it has been seen that extreme and counter examples are not used in these books at all. Start up and improving example are used more frequently in the books that were taught in the years of 2009-2010 and 2015-2016 than the books taught in the years of 2000-2001. It has been seen that start up examples are given more place particularly in the academic years of 2015-2016 and the subject of limits is associated with daily life.